Inflammatory bowel disease and multiple sclerosis - M. Dominguez-Gallego; V. Meca-Lallana; C. Ana Belén (Neurology Perspectives)
Introduction: Inflammatory bowel disease (IBD), which mainly includes Crohn’s disease and ulcerative colitis, is characterised by chronic inflammation in the gastrointestinal tract, triggered and perpetuated by an altered immune response. An association has been established between this condition and other autoimmune diseases, including multiple sclerosis (MS). The prevalence of MS in patients with IBD is 0.2%; the association between the 2 conditions is attributed to shared genetic and environmental pathogenic mechanisms. Development: In patients presenting with both diseases, several considerations should be taken into account when selecting the most appropriate treatment. Regarding MS treatment, interferons have been associated with worsening of IBD symptoms, whereas such monoclonal antibodies as rituximab and ocrelizumab may cause gastrointestinal toxicity, and alemtuzumab is not recommended due to increased risk of autoimmune complications. Natalizumab and sphingosine 1-phosphate modulators, such as ozanimod, constitute safer and more effective options for patients with IBD.Regarding treatments for IBD, TNF-α antagonists are contraindicated in patients with MS due to the associated risk of central nervous system demyelination. Vedolizumab and ustekinumab are the recommended alternatives in these cases. Conclusions: Though weak, the association between IBD and MS should be acknowledged; preferably, management of these patients should include medications that treat both conditions simultaneously. Resumen: Introducción: La enfermedad inflamatoria intestinal (EII), que incluye principalmente la enfermedad de Crohn y la colitis ulcerosa, se caracteriza por producir una inflamación crónica en el tracto gastrointestinal, que se inicia y perpetua por alteraciones en la respuesta inmunitaria. Existe una asociación entre esta patología y otras enfermedades autoinmunes, entre ellas la esclerosis múltiple (EM). La prevalencia de EM en pacientes con EII es del 0,2%, atribuyendo esta relación a diferentes mecanismos patogénicos comunes, tanto genéticos como ambientales. Desarrollo: En pacientes con coexistencia de ambas entidades deben tenerse en cuenta diferentes consideraciones en la elección del tratamiento. En relación a los fármacos empleados en la EM el uso de interferones se ha asociado con empeoramiento de síntomas en la EII, anticuerpos monoclonales como rituximab u ocrelizumab podrían causar toxicidad gastrointestinal y alemtuzumab no se recomienda por el riesgo de inducir fenómenos de autoinmunidad. Natalizumab y fármacos moduladores del receptor de esfingosina 1 fosfato como ozanimod, serían opciones de tratamiento más seguras y eficaces en pacientes con EII. Con respecto a los tratamientos empleados en la EII los antagonistas del factor de necrosis tumoral alfa están contraindicados en pacientes con EM, por su asociación con la aparición de lesiones desmielinizantes del sistema nervioso central. En este caso son recomendables fármacos como vedolizumab y ustekinumab. Conclusiones: Aunque la asociación entre ambas patologías es baja, es importante conocerla, siendo preferible elegir un tratamiento que permita una terapia común para ambas patologías.